The basle Committee's proposals for a new capital adequacy assessment framework: a critique - Hall, Maximilian J.B. (PSL Quarterly Review, 2012)
In June 1999, the Basle Committee of Banking Supervisors issued a consultative paper proposing the introduction of a new framework for the capital adequacy assessment of internationally-active banks operating in the G10 area. The initiative reflected a desire to address some of the long-acknowledged deficiencies in the current regime, operating under the guise of the Basle Capital Accord since 1988, and to accommodate recent market developments (especially in risk management) and financial innovations. This article critically analyses the new proposals, as amended in January 2001, providing a "cost-benefit" analysis of the proposed framework and assessing the extent to which the flaws in the current assessment regime would be overcome. JEL Codes: G21, G28, F23